The Performance of Four Different Mineral Liners on the Transportation of Chlorinated Phenolic Compounds to Groundwater in Landfills - Elanur Adar; Mehmet Sinan Bilgili (The Scientific World Journal)
The aim of this study was to investigate the efficiency of four different mineral liners (clay, bentonite, kaoline, and zeolite) which could be utilized to prevent the transport of phenolic compounds to groundwater through alternative liner systems. Four laboratory-scale HDPE reactors with 80 cm height and 40 cm inner diameter were operated for a period of 180 days. Results indicated that the transport of mono- or dichlorophenols is significantly prevented by the liner systems used, while the transport of highly chlorinated phenolic compounds cannot be prevented by the landfill liner system effectively. Highly chlorinated phenolic compounds in groundwater can be found in higher concentrations than the leachate, as a result of the degradation and transformation of these compounds. Thus, the analysis of highly chlorinated phenolic compounds such as 2,4,6-TCP, 2,3,6-TCP, 3,4,5-TCP, and PCP is of great significance for the studies to be conducted on the contamination of groundwater around landfills.